2004
DOI: 10.1023/b:ifla.0000039557.33267.65
|View full text |Cite
|
Sign up to set email alerts
|

Murine Model for Non-IgE-Mediated Asthma

Abstract: Abstract-There is increasing evidence that inflammatory mechanisms other than atopy or eosinophilic inflammation may be involved in the pathogenesis of asthma. The mechanisms associated with non-atopic (non-IgE) or neutrophil-mediated asthma are poorly investigated. Nonatopic airway inflammation and hyperresponsiveness was induced in mice by skin sensitization with dinitrofluorobenzene (DNFB) followed by intra-airway challenge with dinitrobenzene sulfonic acid (DNS). Acute bronchoconstriction and mast cell act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…At the end of this study, the diagnosis of BA was confirmed in 15% and the allergic character of BA was detected in 6% of CVID patients. The results of both studies are consistent with the notion that IgE is not necessary for the development of BA, which has also been shown in mouse models [39]. We therefore conclude that BA may develop, even in a setting of humoral immunodeficiencies, with disturbed IgE production.…”
Section: Discussionsupporting
confidence: 91%
“…At the end of this study, the diagnosis of BA was confirmed in 15% and the allergic character of BA was detected in 6% of CVID patients. The results of both studies are consistent with the notion that IgE is not necessary for the development of BA, which has also been shown in mouse models [39]. We therefore conclude that BA may develop, even in a setting of humoral immunodeficiencies, with disturbed IgE production.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, a late asthmatic response with the continuation of airway obstruction and the development of airway inflammation can also be observed. Mast cells play an important role in the early asthmatic response in both atopic and nonatopic human asthma (9,42). Allergen can activate mast cells by cross-linking to high-affinity IgE receptors (Fc⑀RI) (40).…”
mentioning
confidence: 99%
“…The most important is that a correct strain of mice has to be used. Adler et al [84], as well as Duguet et al [85], showed that Penh and airway resistance/compliance are comparable and correlated in BALB/c, but not in C57BL/6 mice, thus, the BALB/c mice were used in our study.…”
Section: Discussionmentioning
confidence: 94%